The creation of social norms under weak institutions - Florian Diekert; Tillmann Eymess; Joseph Luomba; Israel Waichman (University of Heidelberg, Department of Economics, 2020)
Preventing overfishing at Lake Victoria is a typical situation where policies have to rely on norm-based interventions to improve outcomes. Our lab-in-the-field experiment studies how information about high or low levels of previous cooperation affects the creation of social norms in a three-player prisoner's dilemma game with/without a feedback mechanism. The provision of social information succeeds in creating norms of cooperation only if a feedback mechanism is available. Without feedback, social information cannot prevent the decline of cooperation rates. Exploring the role of the reference network, we find that the effect increases with social proximity among participants.
urn:nbn:de:bsz:16-heidok-283096
Keywords: C72; C93; D7; Q22; 330; common pool resource; collective action; social norms; lab-in-the-field experiment